Inverse Estimation of an Annual Cycle of California's Nitrous Oxide Emissions. Issue 9 (7th May 2018) - Jeong, Seongeun; Newman, Sally; Zhang, Jingsong; Andrews, Arlyn E.; Bianco, Laura; Dlugokencky, Ed; Bagley, Justin; Cui, Xinguang; Priest, Chad; Campos‐Pineda, Mixtli; Fischer, Marc L.
Abstract: Nitrous oxide (N2 O) is a potent long‐lived greenhouse gas (GHG) and the strongest current emissions of global anthropogenic stratospheric ozone depletion weighted by its ozone depletion potential. In California, N2 O is the third largest contributor to the state's anthropogenic GHG emission inventory, though no study has quantified its statewide annual emissions through top‐down inverse modeling. Here we present the first annual (2013–2014) statewide top‐down estimates of anthropogenic N2 O emissions. Utilizing continuous N2 O observations from six sites across California in a hierarchical Bayesian inversion, we estimate that annual anthropogenic emissions are 1.5–2.5 times (at 95% confidence) the state inventory (41 Gg N2 O in 2014). Without mitigation, this estimate represents 4–7% of total GHG emissions assuming that other reported GHG emissions are reasonably correct. This suggests that control of N2 O could be an important component in meeting California's emission reduction goals of 40% and 80% below 1990 levels of the total GHG emissions (in CO2 equivalent) by 2030 and 2050, respectively. Our seasonality analysis suggests that emissions are similar across seasons within posterior uncertainties. Future work is needed to provide source attribution for subregions and further characterization of seasonal variability. Key Points: Multisite observations constrain California's annual N2 O emissions California's N2 O emissions are 1.5–2.5 times a recent state inventory Emissions are similar across seasons within posterior uncertainties